PTPRJ promotes osteoclast maturation and activity by inhibiting Cbl‐mediated ubiquitination of NFATc1 in late osteoclastogenesis. (5th March 2021) - Shalev, Moran; Arman, Esther; Stein, Merle; Cohen‐Sharir, Yael; Brumfeld, Vlad; Kapishnikov, Sergey; Royal, Isabelle; Tuckermann, Jan; Elson, Ari
Abstract : Bone‐resorbing osteoclasts (OCLs) are multinucleated phagocytes, whose central roles in regulating bone formation and homeostasis are critical for normal health and development. OCLs are produced from precursor monocytes in a multistage process that includes initial differentiation, cell–cell fusion, and subsequent functional and morphological maturation; the molecular regulation of osteoclastogenesis is not fully understood. Here, we identify the receptor‐type protein tyrosine phosphatase PTPRJ as an essential regulator specifically of OCL maturation. Monocytes from PTPRJ‐deficient (JKO) mice differentiate and fuse normally, but their maturation into functional OCLs and their ability to degrade bone are severely inhibited. In agreement, mice lacking PTPRJ throughout their bodies or only in OCLs exhibit increased bone mass due to reduced OCL‐mediated bone resorption. We further show that PTPRJ promotes OCL maturation by dephosphorylating the M‐CSF receptor (M‐CSFR) and Cbl, thus reducing the ubiquitination and degradation of the key osteoclastogenic transcription factor NFATc1. Loss of PTPRJ increases ubiquitination of NFATc1 and reduces its amounts at later stages of osteoclastogenesis, thereby inhibiting OCL maturation. PTPRJ thus fulfills an essential and cell‐autonomous role in promoting OCL maturation by balancing between the pro‐ and anti‐osteoclastogenic activities of the M‐CSFR and maintaining NFATc1 expression during late osteoclastogenesis. Abstract : The cytokine RANKL drives monocytes to fuse into polykaryons, which then mature into bone‐resorbing osteoclasts (OCL). We show that protein tyrosine phosphatase PTPRJ promotes OCL maturation by stabilizing the key osteoclastogenic transcription factor NFATc1 during late osteoclastogenesis. PTPRJ fulfills this function by dephosphorylating the M‐CSF receptor and Cbl, thereby reducing the ubiquitination and degradation of NFATc1. Loss of PTPRJ in mice reduces NFATc1 levels, inhibits OCL maturation, and activity and increases bone mass.